2014
DOI: 10.1002/mus.24123
|View full text |Cite
|
Sign up to set email alerts
|

Safety of botulinum toxin for dysphagia in oculopharyngeal muscular dystrophy

Abstract: Introduction Despite multiple studies reporting marked benefit of botulinum toxin (BTX) for treatment of cricopharyngeal dysphagia, little is known about its safety for this indication. We examined the safety of cricopharyngeal BTX for dysphagia in oculopharyngeal muscular dystrophy (OPMD). Methods We reviewed records of patients with OPMD who received cricopharyngeal BTX. Results Twenty-four patients underwent 66 procedures. Overall adverse event frequency was 44%. The most common adverse events were dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
8
0
3
Order By: Relevance
“…Restivo and Marchese-Ragona for their comments on our study. 1 We agree that botulinum toxin (BTX) volume influences local diffusion independently of dose. With identical doses of BTX, there may be greater local diffusion and a larger area of effect when a larger diluent volume (lower concentration) is used, 2 which can lead to adverse events (AEs).…”
mentioning
confidence: 80%
“…Restivo and Marchese-Ragona for their comments on our study. 1 We agree that botulinum toxin (BTX) volume influences local diffusion independently of dose. With identical doses of BTX, there may be greater local diffusion and a larger area of effect when a larger diluent volume (lower concentration) is used, 2 which can lead to adverse events (AEs).…”
mentioning
confidence: 80%
“…[ 13 ] The complication rate reported in literature reviews is, and the reported complication are mainly temporary unilateral vocal cord palsy, [ 14 ] dysphonia, or worsened dysphagia. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…reviewed the health records of their patients with oculopharyngeal muscular dystrophy who had at least 1 cricopharyngeal (CP) botulinum toxin (BTX) injection for treatment of dysphagia. They sought to better characterize the risks associated with CP myotomy by BTX in these patients . The following variables were evaluated: age; gender; dose; procedure type; injection site; and time since last injection .…”
mentioning
confidence: 99%
“…They sought to better characterize the risks associated with CP myotomy by BTX in these patients . The following variables were evaluated: age; gender; dose; procedure type; injection site; and time since last injection . They was found that worsened dysphagia and dysphonia are dose‐related adverse events (AEs) and provide estimates for the magnitude of AE risk at different doses .…”
mentioning
confidence: 99%
See 1 more Smart Citation